Synergistic Induction of Chicken Antimicrobial Host Defense Peptide Gene Expression by Butyrate and Sugars - Yang, Qing; Fong, Li-An; Lyu, Wentao; Sunkara, Lakshmi T.; Xiao, Kan; Zhang, Guolong (Frontiers in Microbiology, 2021)
Antimicrobial resistance is a major concern to public health demanding effective alternative strategies to disease control and prevention. Modulation of endogenous host defense peptide (HDP) synthesis has emerged as a promising antibiotic alternative approach. This study investigated a potential synergy between sugars and butyrate in inducing HDP gene expression in chickens. Our results revealed that sugars differentially regulated HDP expression in both gene- and sugar-specific manners in chicken HD11 macrophage cells. Among eight mono- and disaccharides tested, all were potent inducers of avian β-defensin 9 (AvBD9) gene, but only galactose, trehalose, and lactose significantly upregulated cathelicidin-B1 (CATHB1) gene expression (P < 0.05). The expression of AvBD14 gene, on the other hand, was minimally influenced by sugars. Moreover, all sugars exhibited a strong synergy with butyrate in enhancing AvBD9 expression, while only galactose, trehalose, and lactose were synergistic with butyrate in CATHB1 induction (P < 0.05). No synergy in AvBD14 induction was observed between sugars and butyrate. Although lactose augmented the expression of nearly all HDP genes, its synergy with butyrate was only seen with several, but not all, HDP genes. Mucin-2 gene was also synergistically induced by a combination of lactose and butyrate. Furthermore, lactose synergized with butyrate to induce AvBD9 expression in chicken jejunal explants. Mechanistically, hyper-acetylation of histones was observed in response to both butyrate and lactose, relative to individual compounds. MAPK, NF-κB, and cyclic AMP signaling pathways were also found to be involved in butyrate- and lactose-mediated synergy in AvBD9 induction. Collectively, a combination of butyrate and a sugar with both HDP-inducing and barrier protective activities holds the promise to be developed as an alternative to antibiotics for disease control and prevention.